Matrix metalloproteinases as possible biomarkers of obstructive sleep apnea severity – A systematic review. (August 2019) - Franczak, Aleksandra; Bil-Lula, Iwona; Sawicki, Grzegorz; Fenton, Mark; Ayas, Najib; Skomro, Robert
Summary: Obstructive sleep apnea is an underdiagnosed sleep-related breathing disorder affecting millions of people. Recurrent episodes of apnea/hypopnea result in intermittent hypoxia leading to oxidative stress. Obstructive sleep apnea is considered an independent risk factor for cardiovascular disease but the exact pathophysiology of adverse cardiovascular outcomes of obstructive sleep apnea has not been fully elucidated. Matrix metalloproteinases (MMPs) have been associated with both oxidative stress and cardiovascular diseases. Hypoxic conditions were shown to influence MMP expression, secretion and activity. Moreover, matrix metalloproteinases contribute to ischemia/reperfusion injury. Therefore, action of matrix metalloproteinases can provide a possible molecular mechanism linking obstructive sleep apnea with oxidative stress and cardiovascular disease. The aim of this paper was to review the current evidence of association between matrix metalloproteinases and obstructive sleep apnea with focus on hypoxemia and severity of obstructive sleep apnea.